A Conceptual Modeling Of Ultrasonic Tomography System To Detect Early Caries Lesions - Nurul I’zaaz Mohd Zulkifli; Juliza Jamaludin; Normaliza Ab Mali; Farah Aina Jamal; Nik Halimaton Sadiah Nik Abdul Razak (Universiti Teknologi Malaysia, 2024)
Indexed by WOS/Scopus/ERA